The work identity of leaders in the midst of the COVID-19 pandemic - Meadows, Stephanie; De Braine, Roslyn (Frontiers in Psychology, 2022)
The world of work is being changed at an unprecedented rate as a result of the rise of the Fourth Industrial Revolution. This rate of change was accelerated by the COVID-19 pandemic, which left organizations and their leadership to deal with myriad of challenges. These changes also impacted leaders’ identities in their work and their roles in their organizations. We examine how leaders responded to the various workplace challenges presented by the COVID-19 pandemic and what this meant for their work identities as leaders. To do this, we made use of role identity theory, social identity theory, and leader identity. A qualitative study was conducted with a group of eight senior leaders from various South African and global organizations who had between five and 10 years’ work experience, and some had even more. Data were collected through semi-structured interviews, conducted virtually and in person. Thematic analysis was used to analyze the data. The main finding that emerged from the research was that leaders employed virtual leadership to ensure that customers’ expectations were met, and to manage team-and organizational performance. These leaders achieved this by fostering a digital culture and building effective teams. They achieved their leadership goals by ensuring social identity continuity amongst their teams. This required them taking on extra roles, such as strategist, technology expert, entrepreneur, coach, mentor, and member of the team. Their leader role identity, as part of their work identity, was amplified by the pandemic. The implication is that organizations should develop leadership development programs to increase and strengthen leader identities to capacitate them for times of crisis.